The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5539/jas.v10n12p479
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Stock Under Different Types of Land Use in a Seasonally Dry Tropical Forest

Abstract: The aim of this study, was to analyse the effect of cover vegetation change on stocks of Total Organic Carbon (ST.TOC) and Total Nitrogen (ST.TN) in soils of a Seasonally Dry Tropical Forest in the Brazilian semi-arid region. The study was carried out on three farms located on a typical Orthic Chromic Luvisol in an SDTF. Soil samples were collected from trenches, 70 × 70 cm in size, in the 0-10, 10-20, 20-30, 30-40, 40-60 and 60-80 cm layers, under four types of land use: dense Caatinga (DC), open Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results also show that the quantity and quality of the residues were less significant for the increase SOC stocks than the tillage regime. Our results are supported by several studies for the semi-arid regions (García-González et al, 2018;Pereira Filho et al, 2019;Zhang et al, 2013) that demonstrated an increase in total SOC stocks promoted by changes in land management (Aquino et al, 2017;Valbrun et al, 2018).…”
Section: Future Soc Under Intensified Multifunctional Agroecosystemssupporting
confidence: 89%
See 1 more Smart Citation
“…The results also show that the quantity and quality of the residues were less significant for the increase SOC stocks than the tillage regime. Our results are supported by several studies for the semi-arid regions (García-González et al, 2018;Pereira Filho et al, 2019;Zhang et al, 2013) that demonstrated an increase in total SOC stocks promoted by changes in land management (Aquino et al, 2017;Valbrun et al, 2018).…”
Section: Future Soc Under Intensified Multifunctional Agroecosystemssupporting
confidence: 89%
“…We used experimental evidence for different cover crop mixtures and soil tillage for perennial (Mango) and annual crops (Melon) in irrigated dryland ecosystems. This partially reversed the impact of deforestation and conventional agricultural systems that had reduced the SOC stocks in the semi-arid region (Sacramento et al, 2013;Santana et al, 2019;Valbrun et al, 2018). The conversion of Caatinga forest into mixed arable and perennial (date palms) agriculture had caused an exponential carbon loss during a period of years.…”
Section: Land Use and Agroecosystems Design To Increase Soil Carbon Stocksmentioning
confidence: 99%
“…The potential contribution of the biomasses to soil carbon stocks ( Figure 10) by the cycling of thin branches in the area (Figures 3 and 4A) was 8.06 Mg ha -1 , 3.4-fold higher that of the litterfall, which is a fraction that naturally cycle carbon and nutrients. This contribution represents approximately 71% of the carbon stocks (11.29 Mg ha -1 ) in the first 10 cm of Luvisols with preserved vegetation in this forest (VALBRUN et al, 2018). Guedes et al (2018) found that the great litterfall production resulted in higher amount of carbon added to the soil in a planted forest of 34 years with eucalyptus and pines when compared to neighboring native forest areas that were more susceptible to fire and illegal cuts.…”
Section: Resultsmentioning
confidence: 86%
“…The highest TOC stock in surface and sub-surface soil depth was recorded in natural forests, followed by natural grassland, and the lowest in paddy fields. Higher TOC stock in natural forests due to high concentrations of OC, as recorded by (Valbrun et al, 2018) and (Singh R. et al, 2021), due to high leaf litter, less soil disturbance, the presence of a high number of heterogeneous plants with different root structures and less organic matter decomposition as compared to other cultivated lands (Nicodemo et al, 2018). Horticultural land use (plantations) recorded higher TOC stocks as compared to agricultural (paddy) soils since plantations add more litter and input of animal manures, whereas, in agricultural lands, removal of biomass and intensive tillage practices reduce the OC (Hu et al, 2020).…”
Section: Effect Of Land Use Systems On Carbon Stocksmentioning
confidence: 95%